The INFLUENCE OF KNOWLEDGE, RELIGIOSITY ON CASH WAQF INTEREST IN TRUST MEDIATION - Kuswanto, Didik Heri; Rahayu, Yayuk Ngesti; Rohman, Taufiq Noor (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This study uses a quantitative approach and random sample technique to investigate the interest of the administrators of the Malang City Sharia Economic Society (MES) in monetary waqf. The study involved 44 active respondents from the Malang City MES board who completed an online questionnaire sent via Google Form. The data obtained were analysed using the Structural Equation Modelling - Partial Least Squares (SEM-PLS) method, utilising Smart PLS software version 4.0. The findings of the hypothesis analysis suggest that interest in cash waqf is significantly influenced by knowledge, trust, and religiosity. Moreover, trust plays a mediating role in the connection between knowledge, religion, and desire in cash waqf. These findings provide additional understanding of the factors that influence interest in cash waqf among individuals.